Effect of Fractal Tones on the Improvement of Tinnitus Handicap Inventory Functional Scores among Chronic Tinnitus Patients: An Open-label Pilot Study - Simonetti,Patricia (2018)
Abstract Introduction Music-based sound therapies become recently a trend in the treatment of tinnitus. Few publications have studied the therapeutic use of fractal tones to treat chronic tinnitus. Objective The aim of this study was to determine the benefits of using fractal tones as a unique sound therapy for chronic tinnitus sufferers. Methods Twelve participants were recruited; however, six could not be assigned. At baseline and at 1, 3 and 6 months, the participants were provided with the Tinnitus Handicap Inventory (THI) and Hearing Handicap Inventory for Adults (HHIA) questionnaires, and their visual analog scale score was recorded. Tinnitus pitch and loudness matching was performed before fitting and after 6 months of use. Results The visual analog scale (VAS) score, pitch and loudness matching and minimal masking levels did not result in significant improvement at the end of the treatment. The mean THI measured at baseline was 45, and the final one was 25. A paired sample t-test showed that this 20-point difference was statistically significant. Conclusions We measured the benefits of using fractal tone therapy for the treatment of chronic tinnitus and found that most of the benefits were in the THI functional domain, which includes concentration, reading, attention, consciousness, sleep, social activities, and household tasks. For all patients with bothersome chronic tinnitus and high scores on the THI functional scale, fractal tones should be considered a promising initial sound therapy strategy. The findings from this open-label pilot study are preliminary, and further trials are needed before these results can be generalized to a larger tinnitus population.